TCF3 Regulates the Proliferation and Apoptosis of Human Spermatogonial Stem Cells by Targeting PODXL - Zhou, Dai; Fan, Jingyu; Liu, Zhizhong; Tang, Ruiling; Wang, Xingming; Bo, Hao; Zhu, Fang; Zhao, Xueheng; Huang, Zenghui; Xing, Liu; Tao, Ke; Zhang, Han; et al. (Frontiers in Cell and Developmental Biology, 2021)
Spermatogonial stem cells (SSCs) are the initial cells for the spermatogenesis. Although much progress has been made on uncovering a number of modulators for the SSC fate decisions in rodents, the genes mediating human SSCs remain largely unclear. Here we report, for the first time, that TCF3, a member of the basic helix-loop-helix family of transcriptional modulator proteins, can stimulate proliferation and suppress the apoptosis of human SSCs through targeting PODXL. TCF3 was expressed primarily in GFRA1-positive spermatogonia, and EGF (epidermal growth factor) elevated TCF3 expression level. Notably, TCF3 enhanced the growth and DNA synthesis of human SSCs, whereas it repressed the apoptosis of human SSCs. RNA sequencing and ChIP assays revealed that TCF3 protein regulated the transcription of several genes, including WNT2B, TGFB3, CCN4, MEGF6 and PODXL, while PODXL silencing compromised the stem cell activity of SSCs. Moreover, the level of TCF3 protein was remarkably lower in patients with spermatogenesis failure when compared to individuals with obstructive azoospermia with normal spermatogenesis. Collectively, these results implicate that TCF3 modulates human SSC proliferation and apoptosis through PODXL. This study is of great significance since it would provide a novel molecular mechanism underlying the fate determinations of human SSCs and it could offer new targets for gene therapy of male infertility.